Influences of porosity and tangential edge constraint on thermo-torsional postbuckling of FGM toroidal shell segments surrounded by an elastic medium (Archives of Mechanics - Test, 2023)
For the first time, simultaneous influences of porosities, tangential constraints of boundary edges, surrounding elastic media and elevated temperature on the buckling and postbuckling behaviors of a functionally graded toroidal shell segment are investigated in this paper. Porosities exist in the functionally graded material (FGM) according to even and uneven distributions. Properties of constituent materials are assumed to be temperature dependent and effective properties of the porous FGM are determined using a modified rule of mixture. Governing equations are based on the classical shell theory taking into account geometrical nonlinearity and interactive pressure from surrounding elastic medium. Multi-term analytical solutions are assumed to satisfy simply supported boundary conditions and the Galerkin method is adopted to derive nonlinear load – deflection relations and buckling loads. Parametric studies are carried out to analyze the effects of porosity, shell geometry, degree of tangential edge constraint, elevated temperature and elastic media on the buckling resistance and postbuckling strength of toroidal shell segments under a torsional load. The study reveals that tangential edge restraints have considerably beneficial and detrimental influences on the nonlinear stability of torsion-loaded FGM shells at room and elevated temperatures, respectively. The results also find out that the shear layer and the elastic layer of surrounding medium significantly enhances and alleviates the buckling resistance capacity and severity of the snap-through response of the torsion-loaded porous FGM toroidal shell segment, respectively.